Traditional Healing Practices in Rural Nepal - Baniya, Richa (Journal of Patan Academy of Health Sciences, 2015)
Traditional healing practices in rural Nepal has emerged together with its culture and tradition. In the rural areas traditional culture is still predominant and western allopathic medicine has yet to reach those areas. People of rural societies are reluctant to accept changes in their cultural practices. There are also a lot of factors that make people choose traditional healers in lieu of modern hospital/heath post services. However, modern health services are slowly replacing traditional healing practices in rural parts of Nepal. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13019 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):52-53